Effects of ampelopsin E towards the invasiveness of triple negative breast cancer cell line, MDA-MB-231 - Tieng, Francis Yew Fu (2019)
Breast cancer is the most common cancer and the second leading cause of cancer-related deaths in women. Its two distinctive hallmarks are rapid abnormal growth and the ability to invade and spread (metastasis). During metastasis, the cancer cells form actin-rich protrusions, called invadopodia, which degrade extracellular matrix. The current breast cancer treatment, in particular chemotherapy, comes with adverse effects like immunosuppression, development of cancer resistance and secondary tumour formation. Hence, naturally-occurring molecules claimed to be less toxic are being studied as new drug candidates. Ampelopsin E, extracted from Dryobalanops species, exhibited various pharmacological properties including anticancer and anti-inflammation. Previous study reported that ampelopsin E exhibited strong cytotoxicity against the triple negative breast cancer (TNBC) cell line, MDA-MB-231. However, there is yet any scientific evidence of the effects of ampelopsin E towards metastasis. The objective of this study was to determine the effects of ampelopsin E towards the invasiveness of TNBC cells, MDA-MB-231. To prevent ampelopsin E from causing excessive cell death, the IC20 (concentration that caused 20% inhibition of cell growth compared to the untreated group) of ampelopsin E at 24 hours (17.92 ± 2.3 μM) was determined using 3-[4,5-dimethlthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Ampelopsin E was proven to halt the rate of migration of MDA-MB-231 cells treated with ampelopsin E through scratch assay at 8, 16 and 24 hours in both untreated group and serum-starved conditions. At 24 hours, a significant (p<0.05) reduction pattern was found in the transmigration and invasion of MDA-MB-231 cells when treated with 3.75, 7.5 and 15 μM of ampelopsin E as compared to untreated group. Invadopodia and gelatin degradation assays revealed a significant (p<0.05) inhibition effect of ampelopsin E towards invadopodia formation and their gelatin degradation capability in a concentration-dependent manner in all concentrations (1.88, 3.75, 7.5 and 15 μM) when compared to untreated group. Analysis of the proteins involved in metastasis and invadopodia formation showed that ampelopsin E reduced concentration of matrix metalloproteases (MMP2, MMP9 and MMP14) and platelet-derived growth factor (PDGF) in MDA-MB-231 cells treated with ampelopsin E. In conclusion, ampelopsin E reduced the invasiveness of MDA-MB-231 cells and was proven to be a potential alternative in treating TNBC.